Grammar essentials for dummies - Woods, Geraldine (--For dummies., 2019)
Grammar Essentials For Dummies (9781119589617) was previously published as Grammar Essentials For Dummies (9780470618370). While this version features a new Dummies cover and design, the content is the same as the prior release and should not be considered a new or updated product. For students competing for the decreasing pool of college scholarships, writing a stellar entrance essay can make all the difference. With discrete explanations of vital grammar rules, common usage errors, and the other key concepts people need to refer to most often, Grammar Essentials For Dummies provides crucial information to help students communicate accurately and effectively. This guide is also a perfect reference for parents who need to review critical grammar concepts as they help students with homework assignments or college entrance essays, as well as for adult learners headed back into the classroom and people learning English as a next language. The Essentials For Dummies Series Dummies is proud to present our new series, The Essentials For Dummies. Now students who are prepping for exams, preparing to study new material, or who just need a refresher can have a concise, easy-to-understand review guide that covers an entire course by concentrating solely on the most important concepts. From algebra and chemistry to grammar and Spanish, our expert authors focus on the skills students most need to succeed in a subject.